Polish Crime Literature After 1989 - Adam Mazurkiewicz (Belphégor)
Nowadays, native crime novel is a cultural phenomenon whose significance cannot be narrowed down only to entertainment. The variety of currents that can be observed, comes from writers inspired by the novels about "crime and punishment", by various aesthetics and stylistics. They also do not restrict themselves to presenting the crime in modern scenery, but they choose the historical background. The very act of creating a crime novel became one of the themes as well, which indicates a reflective attitude of writers towards the possibilities offered by literature. The present draft constitutes an attempt of systematising the phenomena characteristic for Polish literary creation, which portray the obscure world of crime.